State Planning for Water Resources - Stover, Susan (Kansas State University, 2012)
Kansas has geographically diverse water resources varying from primarily surface water in the Southeast to primarily ground water in the west. Sedimentation is having a negative impact on the capacity of many of the state’s surface water reservoirs including John Redmond Reservoir which supplies Coffey County Lake which in turn provides cooling water for the Wolf Creek Generating Station. Much of the Ogallala High Plains Aquifer has been drawn down between 2011 and 2012, in some parts by as much as 10 feet on average. The increased need for irrigation during successive drought years has raised some serious concerns about future water availability especially considering the slow recharge rate of the aquifer. New legislation was passed in 2012 to help conserve the aquifer. This legislation changed the “Use it or Lose it” requirement which encouraged inefficient water use and developed an option for Local Enhanced Management Area (LEMA) Conservation Plans to address water conservation needs. In Sheridan County High Priority Area #6 local producers have collectively decided to limit water right use to 55 inches over a 5 year period.
Keywords: Water resources; Reservoir capacity; Ogallala High Plains Aquifer; Water legislation